Regulation of Caenorhabditis elegans p53/CEP-1-dependent germ cell apoptosis by Ras/MAPK signaling. - Rachael Rutkowski; Robin Dickinson; Graeme Stewart; Ashley Craig; Marianne Schimpl; Stephen M Keyse; Anton Gartner (PLoS Genetics)
Maintaining genome stability in the germline is thought to be an evolutionarily ancient role of the p53 family. The sole Caenorhabditis elegans p53 family member CEP-1 is required for apoptosis induction in meiotic, late-stage pachytene germ cells in response to DNA damage and meiotic recombination failure. In an unbiased genetic screen for negative regulators of CEP-1, we found that increased activation of the C. elegans ERK orthologue MPK-1, resulting from either loss of the lip-1 phosphatase or activation of let-60 Ras, results in enhanced cep-1-dependent DNA damage induced apoptosis. We further show that MPK-1 is required for DNA damage-induced germ cell apoptosis. We provide evidence that MPK-1 signaling regulates the apoptotic competency of germ cells by restricting CEP-1 protein expression to cells in late pachytene. Restricting CEP-1 expression to cells in late pachytene is thought to ensure that apoptosis doesn't occur in earlier-stage cells where meiotic recombination occurs. MPK-1 signaling regulates CEP-1 expression in part by regulating the levels of GLD-1, a translational repressor of CEP-1, but also via a GLD-1-independent mechanism. In addition, we show that MPK-1 is phosphorylated and activated upon ionising radiation (IR) in late pachytene germ cells and that MPK-1-dependent CEP-1 activation may be in part direct, as these two proteins interact in a yeast two-hybrid assay. In summary, we report our novel finding that MAP kinase signaling controls CEP-1-dependent apoptosis by several different pathways that converge on CEP-1. Since apoptosis is also restricted to pachytene stage cells in mammalian germlines, analogous mechanisms regulating p53 family members are likely to be conserved throughout evolution.